Antioxidant and Antibacterial Activities of the species Silene inflata Sm.: Biological activities of S. inflata - Mouffouk, Chaima; Mouffouk, Soumia; Dekkiche, Samia; Hambaba, Leila; Mouffouk, Sara (PSM Biological Research, 2019)
This study is devoted to the estimation of total phenolic content and the evaluation of in vitro antioxidant and antibacterial activities of crude extracts (petroleum ether, ethyl acetate and methanolic) obtained from the species Silene inflata Sm. The total phenolic content of the obtained extracts was estimated spectrophotometrically by the Folin-Ciocalteu method, the antioxidant activity was determined by scavenging of the free radical DPPH. Furthermore, the antibacterial activity was assessed by agar disk diffusion assay against four bacterial strains. The results of the phytochemical screening of crude extracts revealed the presence of several types of secondary metabolites including steroids, alkaloids, tannins, polyphenols and saponins. The ethyl acetate extract recorded the highest content of polyphenols (8.60 ± 0.01 µg GAE/mg of plant extract) followed by the methanolic and petroleum ether extracts respectively. The results of the antioxidant activity showed that all the tested extracts had the ability to scavenge the free radical DPPH and possess antioxidant activity in a dose-dependent manner. The methanolic extract has a strong antioxidant activity with an IC50 value of 23.53 ± 0.15 ?g/ml. The crude extracts (petroleum ether and ethyl acetate) had no antibacterial effect against all the tested strains compared to penicillin and gentamicin as positive controls. While the methanolic extract revealed an antibacterial effect only against the clinical strain Staphylococcus albus with a value of the minimum inhibitory concentration at 0.5 mg/ml. In conclusion, the species Silene inflata Sm. could be an important source of new therapeutic agents against pathological damage due to free radicals and microbial infections.